Changing classes : stratification and mobility in post-industrial societies - Esping-Andersen, Gosta (London : Sage Publications, 1993)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: sociale klassen; arbeidersklasse; sociale wetenschappen